Tradition, Innovation, Re-enactment: Hans Talhoffer's Unusual Weapons - Elema Ariella (Bern Open Publishing, 2019)
Multiple manuscripts of Hans Talhoffer's fifteenth-century Fechtbuch depict duels between combatants wielding faceted clubs and tall shields, as well as combatants in tight-fitting grey clothing, and duels between a man and a woman. Legal ordinances and court records from Talhoffer's time and before him provide context for these scenarios and this equipment. Customary law regarding judicial duels varied significantly between German regions. It also changed over time, shaped by influences that sometimes originated well outside German-speaking lands. Talhoffer's work and the Fechtbücher that followed him reflect a practice that spanned multiple regions, preserving fading traditions while embracing new innovations.